Isolated Posterior Element Spinal Tuberculosis, Its Management, and Our Experience with Novel Technique of Flipped Repositioning Laminoplasty: A Retrospective Cohort Study - Sumit Kumar; Ravi Sreenivasan; Atul Sareen; Manu B. B. Gowda; Mohit Kumar Patralekh; Tankeswar Boruah; Narendra Kumar (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Isolated posterior element tuberculosis is atypical and rare with reported incidence of <5% of total cases of spinal tuberculosis. Laminectomy is the classical workhorse for surgical management of these lesions. In this study, we describe the clinical features, diagnosis, and management of isolated posterior element tuberculosis with emphasis on a novel technique of flipped repositioning laminoplasty. Methodology: In this retrospective and follow-up study, clinical and radiological records of confirmed cases of isolated posterior element tuberculosis were taken from the hospital database from January 2015 to January 2020 and patients with minimum 18 months of follow-up at the time of study were included. Patients’ chief complaints at presentation, level of vertebral involvement, part of vertebra involved, presence of posterior epidural abscess, neurology at the time of presentation and treatment given were noted. Results: Records of 25 patients were reviewed. The median age of presentation was 28 (8–48) years. The most common presenting complaints were backache and weakness of both lower limbs. Thoracic spine was most commonly involved, that is in 19 patients. Ten patients were managed on antitubercular therapy alone and recovered fully. Fifteen patients required decompressive surgery in which flipped repositioning laminoplasty was done in 11 patients and laminectomy was done in four patients. Conclusion: Atypical presentation of isolated posterior spinal element tuberculosis and lack of findings on radiographs in early stages often causes delay in diagnosis. Flipped repositioning laminoplasty is an effective technique of decompression that provides adequate exposure and additional stability postoperatively.